Estudo de transições de fase em cristais de l-alanina + ácido oxálico - Vilela, Rivelino Cunha (2013)
In the present word we have studied the effect of temperature on the Raman spectra of crystals of L-alanine + oxalic acid, C3H8NO2+.C2HO4-. Raman spectroscopy measurements were performed on polycrystalline samples at different temperatures varying in the range from room temperature to T = 20 K; a tentative assignment of all normal modes was furnished. In order to help the understanding of the crystal behavior we have also obtained X-ray diffractograms and studied the dependence of lattice parameters through dilatometry as a function of temperature in the 290 K – 93 K range. The three different techniques allowed us to construct a picture of the material under low temperature conditions. As a consequence we have realized that L-alanine + oxalic acid crystal undergoes three phase transitions at low temperatures. The splitting of a band at 90 cm-1 and an anomaly in one of the lattice parameters are the signature for the first phase transition that is observed at 250 K. At 150 K it was observed the appearance of two new bands in the Raman spectrum and, simultaneously, it was observed change in the curves of a and c lattice parameters. Additionally, it was verified the appearance of new peaks in the X-ray diffractogram at the same temperature, characterizing the second phase transition. At a temperature even lower, at about 43 K, it was verified the occurrence of the third phase transition that has as main characteristic the splitting of two bands that are associated to the lattice modes. Changes in the modes associated with CH3 and NH3+ during the cooling is discussed. An important behavior of the crystal with the cooling process was the red shift of the band of lower frequency, similar to the soft-mode vibration of ferroelectric materials, although the frequency of the mode in L-alanine + oxalic acid does not goes to zero. Based on the results on Raman spectroscopy, dilatometry and X-ray diffraction, and on the possible symmetry sites occupied by the molecules through the O=CC group in the various phases, it is suggested the following sequence of phase transitions D24 → C2h5 → Cs3 → C23, which should occur at 250 K, 150 K and 43 K.